The Stock Markets Reaction to Strict Environmental Inspection: Evidence from Heavily Polluting Listed Companies in China - Tingting, Xie; Yong, Wang (UUM Press, 2020)
As an important part of the new environmental governance system in China, the policy effect of Central Environmental Inspection has gained more attention. Based on the data from heavily polluting listed companies in China, this paper examines the impact of Central Environmental Inspection on corporate value by using an event study approach. The result of the study demonstrates that the Central Environmental Inspection causes a general and significant negative impact on the corporate value of heavily polluting listed companies. More specifically, the market value of private firms and small-scale firms declined more than that of state-owned firms and big-scale firms. In addition, under the deterrent of the Central Environmental Inspection, political connections have no longer become the effective way for polluting firms to evade strict environmental regulation.